Carbon transfer film

JP7637628B2Active Publication Date: 2025-02-28DAICEL CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021546924
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-16
Filing Date
2020-09-16
Publication Date
2025-02-28
Estimated Expiration
2040-09-16

AI Technical Summary

Benefits of technology

【0026】 本開示の炭素移着膜および本開示の摺動部材は、摩耗抑制効果と、摩擦低減効果に優れる。特に、本開示の炭素移着膜は、炭素移着膜内の異物となり得るジルコニウムの含有割合が少ないため、容易に形成することができ、さらに薄膜でも優れた摩耗抑制効果および摩擦低減効果を奏する。また、本開示の潤滑剤組成物は、優れた摩耗抑制効果と、摩擦低減効果を付与することができる。そして、優れた摩耗抑制効果および摩擦低減効果により、摺動部材の焼き付きを防止または抑制することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007637628000004
    Figure 0007637628000004
  • Figure 0007637628000005
    Figure 0007637628000005
  • Figure 0007637628000006
    Figure 0007637628000006
Patent Text Reader

Abstract

Provided is a carbon transfer film having an excellent wear suppression effect and an excellent friction reduction effect. A carbon transfer film 12 contains carbon having a sp2 bond, wherein the zirconium content in a surface thereof is 0.6% by mass or less as calculated by an elemental analysis of the surface by SEM-EDX measurement, and the thickness of the carbon transfer film is less than 100 nm. A sliding member 1 is provided with a base material 11 and a carbon transfer film 12 arranged on at least one surface of the base material 11, wherein the carbon transfer film 12 contains carbon having a sp2 bond and has a thickness of less than 100 nm, and the zirconium content in a surface thereof is 0.6% by mass or less as calculated by an elemental analysis of the surface by SEM-EDX measurement. A lubricant composition comprises an organic dispersion medium that serves as a lubricant base material and nano diamond particles that are nano-dispersed in the organic dispersion medium, and has a zirconium content of less than 100 ppm by mass.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a carbon transfer film. This application claims priority from Japanese Patent Application No. 2019-167886, filed on September 16, 2019, the contents of which are incorporated herein by reference. [Background technology]

[0002] 2. Description of the Related Art Currently, members having a sliding surface (hereinafter sometimes referred to as "slide members") are widely used as product materials in various fields including automobiles, machine parts, medical devices, and home appliances.

[0003] Surface modification technology has been attracting attention as a method for improving the tribological properties of sliding components. Non-Patent Document 1 describes how, when a SUS304 substrate and a carbide ball for bearings are slid between each other with graphene oxide dispersion water (graphene oxide concentration: 1 mass%), a tribofilm is formed on the SUS304 substrate, reducing the coefficient of friction. [Prior art documents] [Non-patent literature]

[0004] [Non-Patent Document 1] Tribology Conference 2015 Spring, Himeji, Abstract Collection "Understanding the Friction Mechanism of Graphene Oxide Lubricant Additives" Pages 163-164 Summary of the Invention [Problem to be solved by the invention]

[0005] However, it is described that the tribofilm in Non-Patent Document 1 was not in close contact with the friction surface, and its edge was peeled off, and in fact only a part of the friction surface remained. When such a sliding member is used, the tribofilm is peeled off or disappears from the edge, and there is a problem that a satisfactory wear suppression effect and friction reduction effect cannot be obtained.

[0006] Therefore, the object of the present disclosure is to provide a carbon transfer film having excellent wear suppression effect and friction reduction effect. Another object of the present disclosure is to provide a sliding member having a sliding surface having excellent wear suppression effect and friction reduction effect. Another object of the present disclosure is to provide a lubricant composition that can provide excellent wear suppression effect and friction reduction effect. [Means for solving the problem]

[0007] As a result of intensive research to achieve the above object, the inventors of the present disclosure have found that a transfer film formed on a substrate by sliding the substrate against another member in the presence of a specific lubricant composition has a specific composition and is excellent in wear suppression effect and friction reduction effect. The present disclosure relates to a product completed based on these findings.

[0008] That is, the present disclosure provides 2 The carbon transfer film includes carbon having bonds, has a zirconium content of 0.6 mass % or less as calculated by elemental analysis using SEM-EDX measurement of the surface, and has a thickness of less than 100 nm.

[0009] The carbon transfer film may further comprise sp 3 It is preferable that the carbon atom has a bond. 3 Preferably the bond-bearing carbon is carbon from diamond.

[0010] The above sp 2 Preferably the bond-bearing carbon is carbon from diamond.

[0011] The present disclosure also provides a method for manufacturing a semiconductor device comprising: a substrate; and a carbon transfer film provided on at least one surface of the substrate, The carbon transfer film is sp 2 comprising carbon having bonds and having a thickness of less than 100 nm; The sliding member has a zirconium content of 0.6 mass % or less as calculated from elemental analysis by SEM-EDX measurement of the surface of the carbon transfer film.

[0012] The carbon transfer film may contain components derived from the substrate.

[0013] The present disclosure also provides a lubricant composition comprising an organic dispersion medium as a lubricant base and nanodiamond particles nano-dispersed in the organic dispersion medium, the lubricant composition having a zirconia content of less than 100 ppm by mass.

[0014] The nanodiamond particles are preferably surface-modified nanodiamond particles having a surface modified with a group represented by the following formula (1). -XR 1 (1) [In formula (1), X represents -NH-, -O-, -OC(=O)-, -C(=O)-O-, -NH-C(=O)-, -C(=O)-NH-, or -S-, and the bond extending to the left from X is bonded to the nanodiamond particle. R 1 represents a monovalent organic group, and the atom bonded to X is a carbon atom. However, in formula (1), the molar ratio of carbon atoms to the total amount of heteroatoms selected from the group consisting of nitrogen atoms, oxygen atoms, sulfur atoms, and silicon atoms is 4.5 or more.

[0015] The present disclosure also provides a lubricant composition comprising an organic dispersion medium as a lubricant base, and surface-modified nanodiamond particles nano-dispersed in the organic dispersion medium and surface-modified with a group represented by the following formula (1): -XR 1 (1) [In formula (1), X represents -NH-, -O-, -OC(=O)-, -C(=O)-O-, -NH-C(=O)-, -C(=O)-NH-, or -S-, and the bond extending to the left from X is bonded to the nanodiamond particle. R 1 represents a monovalent organic group, and the atom bonded to X is a carbon atom. However, in formula (1), the molar ratio of carbon atoms to the total amount of heteroatoms selected from the group consisting of nitrogen atoms, oxygen atoms, sulfur atoms, and silicon atoms is 4.5 or more.

[0016] Above R 1is preferably a monovalent organic group that does not have a hydroxy group, a carboxy group, an amino group, a mono-substituted amino group, a terminal alkenyl group, or a terminal epoxy group.

[0017] The organic dispersion medium as the lubricant base is preferably one or more selected from the group consisting of polyol esters, poly-α-olefins, mineral oils, alkylbenzenes, and polyalkylene glycols.

[0018] In the lubricant composition, the content of the nanodiamond particles is preferably 0.01 to 5.0 mass %, and the average dispersed particle size of the nanodiamond particles in the lubricant composition is preferably 2 to 50 nm.

[0019] It is preferable that the content of the nanodiamond particles in the lubricant composition is 0.1 to 2000 ppm by mass, and the average dispersed particle size of the nanodiamond particles in the lubricant composition is 5 to 100 nm.

[0020] The present disclosure also provides a method for producing a slide member having a substrate and a carbon transfer film provided on a surface of the substrate, the method comprising the steps of: The present invention provides a method for producing a sliding member, which comprises sliding the sliding surface of the substrate and the sliding surface of a sliding member relative to one another in the presence of the lubricant composition, thereby transferring carbon derived from nanodiamond particles in the lubricant composition onto the substrate, thereby forming the carbon transfer film.

[0021] The method for producing the sliding member may further include transferring a component in the base material onto the base material by the sliding, thereby forming the carbon transfer film.

[0022] The sliding member is preferably made of a metal material.

[0023] The sliding may be carried out under boundary lubrication conditions.

[0024] The present disclosure also provides a piston having the above-mentioned carbon transfer film in a sliding area with a cylinder.

[0025] The present disclosure also provides a cylinder having the above carbon transfer film on a sliding area with a piston. Effect of the Invention

[0026] The carbon transfer film and the sliding member of the present disclosure have excellent wear suppression effect and friction reduction effect. In particular, the carbon transfer film of the present disclosure has a low content of zirconium, which may become a foreign matter in the carbon transfer film, so that it can be easily formed, and even a thin film has excellent wear suppression effect and friction reduction effect. In addition, the lubricant composition of the present disclosure can impart excellent wear suppression effect and friction reduction effect. And, due to the excellent wear suppression effect and friction reduction effect, it is possible to prevent or suppress the seizure of the sliding member. [Brief description of the drawings]

[0027] [Figure 1] FIG. 2 is a partial schematic cross-sectional view of a slide member according to an embodiment of the present disclosure. [Diagram 2] 1A to 1C are explanatory views showing an example of a method for manufacturing a sliding member having a carbon transfer film formed thereon according to an embodiment of the present disclosure. [Diagram 3] 1 is a graph showing the change in friction coefficient from the start to the end of transfer film formation in Example 2. [Figure 4] 11 is a graph showing the change in friction coefficient from the start to the end of transfer film formation in Comparative Example 2. [Diagram 5] 1 is a cross-sectional profile obtained when determining the wear cross-sectional area of ​​the transfer film in Example 2. [Figure 6] 13 is a cross-sectional profile obtained when determining the wear cross-sectional area of ​​the transfer film of Comparative Example 2. [Figure 7] 1 is a Raman spectrum of the transfer film of Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] [Carbon transfer film] The carbon transfer film of the present disclosure is sp 2The carbon transfer film contains carbon having bonds, has a zirconium content of 0.6 mass% or less as calculated by elemental analysis using SEM-EDX measurement of the surface, and has a thickness of less than 100 nm. In this specification, the carbon transfer film may be referred to as "carbon transfer film (X)".

[0029] In this specification, the term "surface" refers to a surface that becomes the sliding surface of the movable part of the sliding member during sliding. In addition, in this specification, the term "carbon transfer film" is a concept that includes a coating formed by adhesion of wear powder (also called transfer particles) generated from at least one of two sliding members to the surface of the other member, and a coating (so-called tribofilm) formed by adsorption of additives contained in a lubricant or wear powder to the sliding surface or by a chemical reaction. In other words, the carbon transfer film (X) is composed of a film formed from the wear powder containing carbon and / or the tribofilm containing carbon.

[0030] The carbon transfer film (X) is sp 2 It contains carbon with bonds, i.e., sp 2 The carbon transfer film (X) further contains carbon having a sp bond. 3 In this case, the carbon transfer film (X) may contain carbon having sp bonds corresponding to the graphite structure. 2 Carbon with bonds and sp corresponding to the diamond structure 3 Carbon atoms having bonds are mixed in.

[0031] Carbon transfer film (X) is sp 3 Carbon with bond and sp 2 When the carbon transfer film (X) contains carbon having a bond, the above sp 2 Carbon with bond and the above sp 3 The above sp 3 The ratio of carbons with bonds sp 3 / (sp 2 +sp 3) is not particularly limited, but is preferably 0.2 or less, more preferably 0.1 or less, and even more preferably less than 0.1. When the ratio is 0.2 or less, the carbon transfer film has excellent low wear properties. In addition, the ratio is a value exceeding 0, for example, 0.01 or more.

[0032] The above ratio sp 3 / (sp 2 +sp 3 ) can be evaluated using the Raman spectrum obtained by Raman spectroscopy. When evaluating carbon materials using Raman spectroscopy, the peak corresponding to the diamond structure is identified as sp 3 The two peaks of the D (Disorder) band and G (Graphite) band, which correspond to the bonded carbon and graphite structure, are sp 2 The peak intensity ratio of the carbon atoms having bonds is used as an index to determine the peak intensity.

[0033] That is, the above ratio sp 3 / (sp 2 +sp 3 ) is the region of the Raman spectrum obtained by Raman spectroscopy, 1320-1330 cm -1 The area intensity (I) of the peak corresponding to the diamond structure observed in the range of 1300 to 1400 cm -1 The D band peak (hereinafter sometimes referred to as the "D peak") area intensity (Id) observed in the range of 1570 to 1640 cm -1 The ratio I / (Id+Ig+I) of the area intensity (I) of the peak corresponding to the diamond structure to the sum of the area intensity (Ig) of the G band peak (hereinafter sometimes referred to as "G peak") observed in the range can be obtained as an index. 3 / (sp 2 +sp 3 This is because it is believed that Id+Ig+I and the above ratio I / (Id+Ig+I) are correlated values.

[0034] The Raman spectrum can be measured, for example, under the following conditions. Measuring equipment: Microscopic laser Raman spectrometer, product name "LabRAM HR Evolution" (manufactured by Horiba, Ltd.) Measurement light source: 325nm Output power: 1.075mW Exposure time: 4 to 16 seconds Number of times: 2 to 4

[0035] Carbon transfer film (X) is sp 3 Carbon with bond and sp 2 When the carbon transfer film (X) contains carbon having a bond, the carbon transfer film (X) has a Raman spectrum of 1570 to 1640 cm in a Raman spectrum obtained by Raman spectroscopy using a measurement light source of 325 nm. -1 The G band observed in the range of 1300 to 1400 cm -1 It is preferable that the D band is observed in the range of 1580 to 1640 cm. -1 , more preferably 1590 to 1630 cm -1 , particularly preferably 1600 to 1620 cm -1 It is.

[0036] Generally, in Raman spectra, nanodiamonds are sp 3 Carbon with bond and sp 2 It is known that the peaks due to carbon containing bonds are observed. However, the sp 3 The peak intensities due to carbon having bonds and the G band peak intensities are clearly different from the peak intensities of known nanodiamonds.

[0037] In the above Raman spectrum, sp 3 In the case where the carbon transfer film (X) has a peak due to a bond, a D peak, and a G peak, the peak intensity of the G band of the carbon transfer film (X) is 3It is preferable that the peak intensity of the G band of the carbon transfer film (X) is greater than the peak intensity of the D band. In other words, it is preferable that the Raman spectrum of the carbon transfer film (X) has a baseline slope (gradient) that rises to the right. Diamond-like carbon (DLC) is known as a carbon-based material whose Raman spectrum slope rises to the right, and the carbon transfer film (X) has a Raman spectrum waveform that is similar to that of GLC (graphite-like carbon) among DLCs. Although the exact mechanism is unknown, it is speculated that the carbon transfer film (X) is a carbon transfer film that shows a DLC-like Raman spectrum waveform from carbon derived from diamond (nanodiamond). It is also speculated that this has some effect on the expression of the friction reduction effect and wear suppression effect.

[0038] The proportion of zirconium calculated by elemental analysis by SEM-EDX measurement of the carbon transfer film (X) surface is 0.6 mass% or less, preferably 0.3 mass% or less, more preferably 0.1 mass% or less, particularly preferably 500 mass ppm or less, and most preferably not contained. By the proportion of zirconium being 0.6 mass% or less, the content of zirconium that can become a foreign matter in the carbon transfer film is small, so that the formability of the carbon transfer film is excellent and the carbon transfer film can be easily formed. Furthermore, since the content of zirconium that can become a foreign matter in the carbon transfer film is small, even a thin film has excellent wear suppression effect and friction reduction effect.

[0039] The SEM-EDX measurement is performed on the surface of the carbon transfer film (X) in a state where the carbon transfer film (X) is formed on a support such as a substrate. Specifically, an electron beam is irradiated from the surface side of the carbon transfer film (X) formed on the support, characteristic X-rays generated by the electron beam irradiation are detected, and the X-rays are spectroscopically analyzed by energy to perform elemental analysis and composition analysis. Note that when the components of the support are detected and included in the analysis results, it is difficult to distinguish between the components of the carbon transfer film and the components of the support in the analysis results, so the zirconium ratio is calculated from the composition analysis results including the components of the support.

[0040] The SEM-EDX measurement can be performed, for example, under the following conditions. Measuring equipment: Scanning electron microscope, product name "SU5000" (manufactured by Hitachi High-Technologies Corporation), energy dispersive X-ray spectrometer, product name "X-Max50" (manufactured by OXFORD instruments) Acceleration voltage: 5 kV

[0041] The atoms constituting the carbon transfer film (X) include at least carbon, and may include other atoms such as iron, oxygen, chromium, nickel, and silicon.

[0042] The thickness (film thickness) of the carbon transfer film (X) is less than 100 nm. By having the film thickness of less than 100 nm, excellent wear suppression effect and friction reduction effect are obtained even if the film thickness is thin. The thickness may be, for example, 3 nm or more, 5 nm or more, or 10 nm or more.

[0043] The friction coefficient of the surface of the carbon transfer film (X) is preferably low from the viewpoint of friction reduction effect and wear suppression effect, for example, 0.2 or less, preferably 0.17 or less, more preferably 0.16 or less. When the friction coefficient is 0.2 or less, a further low friction effect is obtained.

[0044] The method for measuring the friction coefficient is not particularly limited, and can be appropriately selected depending on the purpose and use of the carbon transfer film, such as a ball (pin)-on-disk rotation test, a ball (pin)-on-disk reciprocating motion test, a thrust cylinder test, a block-on-ring test, a four-ball test, a pin block test, or a vibration friction and wear test.

[0045] For example, the friction coefficient of the surface of the carbon transfer film (X) may be determined by a friction test using the following drop-type ball-on-disk sliding friction tester.

[0046] Friction test: Using a SUJ2 disc, a 10 mm diameter SUJ2 ball with a carbon transfer film formed thereon, and a ball-on-disc type SRV friction tester equipped with a load cell, the ball is caused to slide back and forth against the sliding surface of the disc under conditions of an initial load of 100 N, amplitude of 1.5 mm, frequency of 50 Hz, and time of 20 minutes. The friction force between the disc and the ball is measured using the load cell, and the friction coefficient is calculated by dividing the friction force by the load.

[0047] The carbon transfer film (X) has excellent wear suppression and friction reduction effects. In particular, the carbon transfer film (X) can be easily formed because it contains a small amount of zirconium, which can become a foreign matter in the carbon transfer film, and even a thin film has excellent wear suppression and friction reduction effects. Furthermore, the excellent wear suppression and friction reduction effects can prevent or suppress seizure of the sliding member.

[0048] [Sliding parts] The present disclosure provides a carbon transfer film comprising a substrate and a carbon transfer film disposed on at least one surface of the substrate, the carbon transfer film being formed of a sp 2 The present invention provides a sliding member that contains carbon having bonds, has a thickness of less than 100 nm, and has a zirconium ratio of 0.6 mass% or less calculated by elemental analysis of the carbon transfer film surface by SEM-EDX measurement. The sliding member can be obtained, for example, by forming a carbon transfer film (X) on a substrate. The sliding member may have layers other than the substrate and the carbon transfer film.

[0049] Fig. 1 is a schematic cross-sectional view showing one embodiment of a sliding member of the present disclosure. As shown in Fig. 1, the sliding member 1 includes a substrate 11 and a carbon transfer film 12 provided on the surface of the substrate 11. The sliding member 1 is provided with the carbon transfer film 12 on the entire surface of the substrate 11. The sliding member 1 only needs to have the carbon transfer film 12 on at least an area of ​​the substrate 11 that will become a sliding area, and may have an area without the carbon transfer film 12.

[0050] The substrate is not particularly limited as long as it has the purpose of forming a carbon transfer film to reduce the friction coefficient of the surface of the sliding member. Materials constituting the substrate include known or commonly used materials used for sliding members, such as metals such as iron, copper, aluminum, and titanium, carbon, silicon, and various resins. The substrate may be made of one material or two materials.

[0051] Examples of the substrate include metal materials such as alloy steels, such as carbon steel, chromium steel, and chromium molybdenum steel, alloy tool steel, stainless steel (e.g., SUS), bearing steel (e.g., SUJ), and special-purpose steels, such as spring steel (e.g., SUP); copper plates; aluminum plates; titanium plates; silicon substrates; and carbon films, such as diamond-like carbon (DLC) films. The substrate surface may be subjected to various surface treatments, such as various electrochemical treatments, such as plating, chemical conversion treatments, and anodization; various coatings, such as flow coating and powder coating; and physical surface treatments, such as shot blasting.

[0052] The carbon transfer film on the sliding member is sp 2 The carbon transfer film may contain components derived from the substrate, such as iron, carbon, silicon, etc.

[0053] The zirconium content calculated by elemental analysis by SEM-EDX measurement on the carbon transfer film surface of the sliding member is 0.6 mass% or less, preferably 0.3 mass% or less, more preferably 0.1 mass% or less, particularly preferably 500 mass ppm or less, and most preferably not contained. The zirconium content of 0.6 mass% or less indicates that the content of zirconium that can become foreign matter in the carbon transfer film is small, which makes it possible to easily form the carbon transfer film with excellent formability. Furthermore, since the content of zirconium that can become foreign matter in the carbon transfer film is small, even a thin film has excellent wear suppression and friction reduction effects. The specific method and conditions of the SEM-EDX measurement are the same as those described for the carbon transfer film (X) above.

[0054] The carbon transfer film is preferably the carbon transfer film (X). Moreover, the preferred aspects of the carbon transfer film in the sliding member are the same as the preferred aspects of the carbon transfer film (X).

[0055] The above-mentioned sliding member has excellent friction reducing and wear suppressing effects, and therefore can be preferably used as a material for products in various fields including automobiles, machine parts, medical equipment, and home appliances.

[0056] Examples of the sliding member include a cylinder and a piston. The cylinder has the carbon transfer film (e.g., carbon transfer film (X)) in the sliding area with the piston. The piston has the carbon transfer film (e.g., carbon transfer film (X)) in the sliding area with the piston. Since such cylinders and / or cylinders have the carbon transfer film in their sliding areas, friction and wear are reduced even with repeated sliding, and seizure of the sliding parts is suppressed.

[0057] The sliding member includes the carbon transfer film, which serves as the sliding surface, and therefore has excellent wear suppression and friction reduction effects, and can prevent or suppress seizure of the sliding member.

[0058] [Lubricant composition] The present disclosure provides a lubricant composition comprising an organic dispersion medium as a lubricant base and nanodiamond particles nano-dispersed in the organic dispersion medium, the content of zirconia being less than 100 mass ppm. In this specification, the lubricant composition may be referred to as "lubricant composition (A)". The present disclosure also provides a lubricant composition comprising an organic dispersion medium as a lubricant base and surface-modified nanodiamond particles nano-dispersed in the organic dispersion medium and surface-modified with a group represented by formula (1) described below. In this specification, the lubricant composition may be referred to as "lubricant composition (B)". In addition, the lubricant composition (A) and the lubricant composition (B) may be collectively referred to as "lubricant composition (Y)". By using the lubricant composition (A), the carbon transfer film (X) and the above-mentioned sliding member can be manufactured. Hereinafter, nanodiamond may be referred to as "ND".

[0059] The lubricant composition may be a lubricant composition for initial break-in or may be a lubricant composition for the present lubrication. In this specification, the lubricant composition for initial break-in refers to a composition used to form a low friction surface (break-in surface) in the early stages of a machine having a sliding member. The lubricant composition for initial break-in can, for example, smooth out the unevenness of the surface of the sliding member to make it smooth, or form a modified surface. After the break-in surface is formed, the lubricant composition for initial break-in is removed by washing or the like, and sliding is performed using the lubricant composition for the present lubrication (the lubricant composition for the present lubrication). Here, the lubricant composition for the present lubrication refers to a lubricant that is not removed during operation of the sliding member (during use of the machine) and continues to exist in the sliding part. The lubricant composition for initial break-in can also be used as the lubricant composition for the present lubrication by supplying it to the sliding part again without removing it after the formation of the break-in surface, or by removing it once and then using it as the lubricant composition for the present lubrication.

[0060] The coefficient of friction of the sliding parts when a lubricant is used varies over the hydrodynamic lubrication region, the mixed lubrication region, and the boundary lubrication region depending on the viscosity of the lubricant, the sliding speed, and the load, as shown by the Stribeck curve. In the hydrodynamic lubrication region, the sliding members are separated by a continuous lubricant film, and the distance between the sliding members is considerably larger than the surface roughness of the sliding members. For this reason, the friction resistance in the hydrodynamic lubrication region is mainly due to the internal friction of the lubricant. As the load increases from the hydrodynamic lubrication region and the lubricant film becomes thinner due to the decrease in the sliding speed or the increase in temperature, the friction coefficient increases rapidly, and changes to the boundary lubrication region through the mixed lubrication region. In the boundary lubrication region, the frequency of solid contact between the members increases, and the portion supported by the lubricant film becomes extremely small. For this reason, in the boundary lubrication region, the surface physical properties of the sliding members mainly affect the friction resistance, rather than the physical properties such as the wear resistance of the lubricant. On the other hand, according to the lubricant composition (Y), the friction coefficient in the boundary lubrication region is reduced, and it is also possible to expand the mixed lubrication region and the hydrodynamic lubrication region.

[0061] In the lubricant composition (Y), ND particles are nano-dispersed in an organic dispersion medium as a lubricant base. Most lubricant compositions used as lubricants for sliding parts are oil-based, so by using an organic dispersion medium as a lubricant base, the carbon transfer film (X) can be used in a wide range of applications.

[0062] Examples of the organic dispersion medium as the lubricant base include polyphenyl ether, alkyl benzene, alkyl naphthalene, ester oil, glycol-based synthetic oil, polyolefin-based synthetic oil, and mineral oil. More specifically, examples of the organic dispersion medium include polyα-olefin, ethylene-α-olefin copolymer, polybutene, alkyl benzene, alkyl naphthalene, polyalkylene glycol, alkyl-substituted diphenyl ether, polyol ester, dibasic acid ester, carbonate ester, phosphate ester, silicone oil, fluorinated oil, GTL (Gas to Liquids), and mineral oil. The organic dispersion medium as the lubricant base may be used alone or in combination of two or more.

[0063] As the organic dispersion medium as the lubricant base, polyol esters, poly-α-olefins, mineral oils, alkylbenzenes, and polyalkylene glycols are preferred from the viewpoint of being more effective in reducing the amount of wear of sliding members.

[0064] The lubricant composition (A) has a zirconia content of less than 100 ppm by mass, preferably 20 ppm by mass or less, more preferably 2 ppm by mass or less. When the zirconia content is less than 100 ppm by mass, the carbon transfer film (X) is excellent in formability, and the carbon transfer film can be easily formed on the substrate. In addition, the incorporation of zirconium into the carbon transfer film (X) is suppressed, and even a thin film has excellent wear suppression and friction reduction effects. The lower limit of the zirconia content may be, for example, 0.02 ppm by mass or 0.1 ppm by mass.

[0065] The content of zirconia can be determined by detecting Zr by inductively coupled plasma atomic emission spectroscopy (ICP atomic emission spectroscopy) and based on the amount of Zr detected using a dispersion with a known content as a standard. Zirconia is often mixed into the lubricant composition due to the zirconia beads contained in a bead mill used to break down the aggregates of ND particles and nano-disperse the ND particles. For this reason, a lubricant composition with a low content of zirconia can be obtained by not performing bead milling using zirconia beads or by minimizing the time for performing the bead milling.

[0066] The ND particles contained in the lubricant composition (A) are not particularly limited, and known or conventional ND particles can be used. The ND particles may be surface-modified ND (surface-modified ND) particles, or may be non-surface-modified ND particles. Non-surface-modified ND particles have hydroxyl groups (-OH) on the surface. Only one type of ND particles may be used, or two or more types may be used.

[0067] In the above-mentioned surface-modified NDs, examples of the compound or functional group that modifies the surface of the ND particles include a silane compound, a carboxyl group (-COOH), a phosphonate ion or a phosphonic acid residue, a surface-modifying group having a vinyl group at the end, an amide group, a cation of a cationic surfactant, a group containing a polyglycerin chain, a group containing a polyethylene glycol chain, and other organic groups.

[0068] The ND particles contained in the lubricant composition (A) are preferably surface-modified ND particles whose surfaces are modified with a group represented by the following formula (1). The ND particles contained in the lubricant composition (B) are surface-modified ND particles whose surfaces are modified with a group represented by the following formula (1). -XR 1 (1) [In formula (1), X represents -NH-, -O-, -OC(=O)-, -C(=O)-O-, -NH-C(=O)-, -C(=O)-NH-, or -S-, and the bond extending to the left from X is bonded to the nanodiamond particle. R 1 represents a monovalent organic group, and the atom bonded to X is a carbon atom. However, in formula (1), the molar ratio of carbon atoms to the total amount of heteroatoms selected from the group consisting of nitrogen atoms, oxygen atoms, sulfur atoms, and silicon atoms is 4.5 or more.

[0069] The surface-modified ND surface-modified with the group represented by the above formula (1) can be produced by using a small amount of zirconia, so that the amount of zirconia mixed into the lubricant composition (Y) can be minimized, and the dispersibility in the organic dispersion medium as the lubricant base is more excellent. Also, the obtained carbon transfer film and the friction reduction effect of the sliding member are more excellent.

[0070] In the above formula (1), X represents -NH-, -O-, -OC(=O)-, -C(=O)-O-, -NH-C(=O)-, -C(=O)-NH-, or -S-, and the bond extending to the left from X is bonded to the nanodiamond particle. Note that in each of these listed bonds, the bond extending to the left is bonded to the nanodiamond particle, and the bond extending to the right is R 1Bind to.

[0071] In the above formula (1), R 1 R represents a monovalent organic group, and the atom bonded to X is a carbon atom. 1 The monovalent organic group as R preferably does not have a hydroxy group, a carboxy group, an amino group, a mono-substituted amino group, a terminal alkenyl group, or a terminal epoxy group. In this specification, the term "terminal" in the terminal alkenyl group and the terminal epoxy group includes both the terminal of the main chain and the terminal of the branched chain. 1 The monovalent organic group as above preferably does not have a functional group containing active hydrogen (such as a hydroxy group, a carboxy group, an amino group, a mono-substituted amino group, a thiol group, or a phosphate group). In this specification, the amino group simply referred to as an "amino group" refers to "-NH2", and the "mono-substituted amino group" refers to "-NHR" (R represents a monovalent organic group).

[0072] Above R 1 Examples of the monovalent organic group in include substituted or unsubstituted hydrocarbon groups (monovalent hydrocarbon groups), substituted or unsubstituted heterocyclic groups (monovalent heterocyclic groups), and groups in which two or more of the above monovalent hydrocarbon groups and / or monovalent heterocyclic groups are bonded. The bonded groups may be bonded directly or via a linking group. Examples of the linking group include amino groups, ether bonds, ester bonds, phosphinic acid groups, sulfide bonds, carbonyl groups, organic group-substituted amide groups, organic group-substituted urethane bonds, organic group-substituted imide bonds, thiocarbonyl groups, siloxane bonds, and groups in which two or more of these are bonded.

[0073] Examples of the hydrocarbon group in the monovalent organic group include an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, an aromatic hydrocarbon group, and groups in which two or more of these are bonded together.

[0074] Examples of the aliphatic hydrocarbon group include an alkyl group, an alkenyl group, and an alkynyl group. Examples of the alkyl group include a C group such as a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, a hexyl group, an octyl group, an isooctyl group, a decyl group, and a dodecyl group. 1-22 Alkyl group (preferably C 2-20 Alkyl groups, more preferably C 3-18 Examples of the alkenyl group include C groups such as vinyl group, allyl group, methallyl group, 1-propenyl group, isopropenyl group, 1-butenyl group, 2-butenyl group, 3-butenyl group, 1-pentenyl group, 2-pentenyl group, 3-pentenyl group, 4-pentenyl group, and 5-hexenyl group. 2-22 Alkenyl group (preferably C 4-20 Alkenyl groups, more preferably C 8-18 Examples of the alkynyl group include C alkynyl groups such as ethynyl and propynyl groups. 2-22 Alkynyl groups (preferably C 4-20 Alkynyl groups, more preferably C 8-18 alkynyl groups).

[0075] Examples of the alicyclic hydrocarbon group include C cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, and cyclododecyl groups. 3-12 Cycloalkyl groups; cyclohexenyl groups, etc. 3-12 Cycloalkenyl groups; bicycloheptanyl groups, bicycloheptenyl groups, etc. 4-15 and bridged cyclic hydrocarbon groups.

[0076] Examples of the aromatic hydrocarbon group include C phenyl groups, naphthyl groups, etc. 6-14 Aryl groups (especially C 6-10 Aryl groups).

[0077] Examples of the heterocyclic ring forming the heterocyclic group include aromatic heterocyclic rings and non-aromatic heterocyclic rings. Examples of such heterocyclic rings include 3- to 10-membered rings (preferably 4- to 6-membered rings) having carbon atoms and at least one heteroatom (e.g., oxygen atom, sulfur atom, nitrogen atom, etc.) as atoms constituting the ring, and condensed rings thereof. Specifically, heterocyclic rings containing an oxygen atom as a heteroatom (e.g., 3-membered rings such as oxirane ring; 4-membered rings such as oxetane ring; 5-membered rings such as furan ring, tetrahydrofuran ring, oxazole ring, isoxazole ring, γ-butyrolactone ring; 6-membered rings such as 4-oxo-4H-pyran ring, tetrahydropyran ring, morpholine ring; condensed rings such as benzofuran ring, isobenzofuran ring, 4-oxo-4H-chromene ring, chroman ring, isochroman ring; 3-oxatricyclo[4.3.1.1 4,8 ]Undecane-2-one ring, 3-oxatricyclo[4.2.1.0 4,8 ]nonan-2-one ring and the like), heterocycles containing a sulfur atom as a heteroatom (for example, 5-membered rings such as a thiophene ring, a thiazole ring, an isothiazole ring, a thiadiazole ring, and the like; 6-membered rings such as a 4-oxo-4H-thiopyran ring, and the like; condensed rings such as a benzothiophene ring, and the like), heterocycles containing a nitrogen atom as a heteroatom (for example, 5-membered rings such as a pyrrole ring, a pyrrolidine ring, a pyrazole ring, an imidazole ring, and a triazole ring, and the like; 6-membered rings such as an isocyanuric ring, a pyridine ring, a pyridazine ring, a pyrimidine ring, a pyrazine ring, a piperidine ring, and the like; condensed rings such as an indole ring, an indoline ring, a quinoline ring, an acridine ring, a naphthyridine ring, a quinazoline ring, and a purine ring, and the like).

[0078] Examples of the group in which an aliphatic hydrocarbon group and an alicyclic hydrocarbon group are bonded include a cyclohexylmethyl group and a methylcyclohexyl group. Examples of the group in which an aliphatic hydrocarbon group and an aromatic hydrocarbon group are bonded include C groups such as a benzyl group and a phenethyl group. 7-18 Aralkyl groups (especially C 7-10 aralkyl group), cinnamyl group, etc. 6-10 Aryl-C 2-6 Alkenyl group, tolyl group, etc. 1-4 C such as alkyl-substituted aryl groups and styryl groups 2-4Alkenyl-substituted aryl groups and the like.

[0079] Examples of the group in which two or more of the monovalent hydrocarbon groups and / or monovalent heterocyclic groups are bonded via a linking group include a group in which the monovalent hydrocarbon group and / or the monovalent heterocyclic group is bonded to an alkoxy group, an alkenyloxy group, an alkynyloxy group, an aryloxy group, an aralkyloxy group, an acyloxy group, an alkylthio group, an alkenylthio group, an arylthio group, an aralkylthio group, an acyl group, an alkenylcarbonyl group, an arylcarbonyl group, an aralkylcarbonyl group, an alkoxycarbonyl group, an alkenyloxycarbonyl group, an aryloxycarbonyl group, an aralkyloxycarbonyl group, a dialkylamino group, an acylamino group, an oxetanyl group-containing group, a carbamoyl group, or a group in which two or more of these are bonded to each other.

[0080] The hydrocarbon group in the monovalent organic group may have a substituent, such as a halogen atom (e.g., a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, etc.), a cyano group, an isocyanate group, an isothiocyanate group, etc.

[0081] Above R 1 It is preferable that the hydrocarbon group contains a linear hydrocarbon group having 4 or more consecutive carbon atoms. Examples of such a hydrocarbon group include linear alkylene groups such as tetramethylene, pentamethylene, hexamethylene, heptamethylene, octamethylene, nonamethylene, and decamethylene groups; branched alkylene groups such as 2-ethylhexamethylene groups; linear alkenylene groups such as 1-butenylene, 2-butenylene, 1-pentenylene, 2-pentenylene, and 3-pentenylene groups; branched alkenylene groups such as 2-methyl-2-butenylene groups; alicyclic hydrocarbon groups having 4 or more carbon atoms such as cyclohexyl groups; aromatic hydrocarbon groups having 6 or more carbon atoms such as phenyl groups; and heterocyclic groups containing a structure having 4 or more consecutive carbon atoms such as piperidine rings.

[0082] In formula (1), the molar ratio of carbon atom to the total amount of heteroatoms selected from the group consisting of nitrogen atom, oxygen atom, sulfur atom, and silicon atom is 4.5 or more, preferably 5 or more, more preferably 5.5 or more.By the molar ratio being 4.5 or more, the dispersibility in the organic dispersion medium as the lubricant base is excellent.The molar ratio is not particularly limited, but may be, for example, 22 or less, or 20 or less.

[0083] In formula (1), the number of carbon atoms is preferably 6 to 22, and more preferably 8 to 20. When the number of carbon atoms is 6 or more, the steric hindrance between the surface modifying groups is sufficient, and the surface modifying groups are easily dispersed in the dispersion medium. When the number of carbon atoms is 22 or less, the surface modifying groups are prevented from becoming entangled with each other, and the surface modifying groups are easily dispersed in the dispersion medium.

[0084] Among the above-mentioned monovalent organic groups, preferred are monovalent substituted or unsubstituted hydrocarbon groups, groups in which a monovalent substituted or unsubstituted hydrocarbon group is bonded to an alkoxy group, and groups in which a monovalent substituted or unsubstituted hydrocarbon group is bonded to a dialkylamino group.

[0085] In particular, in the above formula (1), X is preferably -O-, -OC(=O)-, -C(=O)-O-, or -NH-. When X is -O-, -OC(=O)-, or -C(=O)-O-, R 1 is preferably a monovalent substituted or unsubstituted hydrocarbon group (particularly, a monovalent substituted or unsubstituted hydrocarbon group that does not have a hydroxy group, a carboxy group, an amino group, a mono-substituted amino group, a terminal alkenyl group, or a terminal epoxy group), and more preferably a linear or branched hydrocarbon group having 8 to 20 carbon atoms (particularly, a linear or branched hydrocarbon group having 8 to 20 carbon atoms that does not have a terminal alkenyl group).

[0086] When X is -NH-, R 1is preferably a monovalent organic group having 8 to 20 carbon atoms (particularly, a monovalent organic group having 8 to 20 carbon atoms and not having a hydroxy group, a carboxy group, an amino group, a mono-substituted amino group, a terminal alkenyl group, or a terminal epoxy group). 1 is preferably a monovalent organic group containing a linear hydrocarbon group with four or more consecutive carbon atoms (particularly, a monovalent organic group containing a linear hydrocarbon group with four or more consecutive carbon atoms and not having a hydroxy group, a carboxy group, an amino group, a mono-substituted amino group, a terminal alkenyl group, or a terminal epoxy group).

[0087] The ND particles constituting the surface-modified ND preferably contain primary particles of nanodiamond. In addition, secondary particles formed by aggregation (adhesion) of several to several tens of the above primary particles may be contained. In addition, the surface of the surface-modified ND may have one or more types of other surface functional groups (e.g., amino groups, hydroxyl groups, carboxyl groups, etc.) in addition to the group represented by the above formula (1).

[0088] The mass ratio of ND to the group represented by formula (1) in the surface-modified ND [ND / the surface-modified group] is not particularly limited, but is preferably 0.5 or more, more preferably 2.5 or more. The mass ratio is preferably 15.0 or less, more preferably 10.0 or less, even more preferably 7.0 or less, and particularly preferably 5.0 or less. When the mass ratio is 0.5 or more, the properties as a nanodiamond material are not easily impaired. When the mass ratio is 15.0 or less (particularly, 7.0 or less), the degree of modification of the group represented by formula (1) is sufficient, and the dispersibility in an organic dispersion medium as a lubricant base is more excellent. The mass ratio is calculated based on the weight loss rate from 200°C to 450°C measured by thermogravimetric analysis, and the reduced weight is taken as the mass of the group represented by formula (1).

[0089] The above-mentioned surface-modified ND can be produced by a production method including a step (sometimes referred to as a "reaction step") of reacting ND particles having hydroxyl groups or carboxyl groups on the surface, in a nano-dispersed state in water, with a compound represented by the following formula (2) in the presence of an acid catalyst to obtain the surface-modified ND particles. R 2 -YH (2) [In formula (2), Y represents -NH-, -O-, -C(=O)-O-, -C(=O)-NH-, or -S-. 2 represents a monovalent organic group, and the atom bonded to Y is a carbon atom.

[0090] In the above reaction step, ND particles having hydroxy groups and / or carboxy groups on the surface are nano-dispersed in water and then reacted with the compound represented by formula (2) above, and the hydroxy groups and / or carboxy groups in the ND particles are dehydrated and condensed with -H in the compound represented by formula (2) above to obtain surface-modified ND particles.

[0091] The ND particles are not particularly limited, and known or conventional nanodiamond particles can be used. The ND particles have carboxyl groups and hydroxyl groups that are inherently generated during the manufacturing process. Only one type of ND particles may be used, or two or more types may be used.

[0092] As the ND particles, for example, detonation ND (i.e., ND produced by the detonation method) or high-temperature high-pressure ND (i.e., ND produced by the high-temperature high-pressure method) can be used. Among them, detonation ND is preferred because it has better dispersibility in the dispersion medium, that is, the particle size of the primary particles is one digit nanometer.

[0093] The above-mentioned detonation ND includes air-cooled detonation ND (i.e., ND produced by air-cooled detonation method) and water-cooled detonation ND (i.e., ND produced by water-cooled detonation method). Among them, air-cooled detonation ND is preferable because the primary particles are smaller than those of water-cooled detonation ND.

[0094] The detonation may be carried out in an air atmosphere or in an inert gas atmosphere such as nitrogen atmosphere, argon atmosphere, or carbon dioxide atmosphere.

[0095] Specific examples of the compound represented by the above formula (2) include primary amines, alcohols, carboxylic acids, amide compounds, and thiols. Only one type of compound represented by the above formula (2) may be used, or two or more types may be used.

[0096] In the above formula (2), Y represents -NH-, -O-, -OC(=O)-, -NH-C(=O)-, or -S-. Y is selected taking into consideration whether it will react with a hydroxy group or a carboxy group in the ND particle. In each of these listed bonds, the bond extending to the left is R 2 and the bond extending to the right bonds to a hydrogen atom.

[0097] In particular, when the ND particle has a hydroxy group, Y is preferably -NH-, -O-, -C(=O)-O-, -C(=O)-NH-, or -S-. Also, when the ND particle has a carboxy group, Y is preferably -O-.

[0098] In the above formula (2), R 2 represents a monovalent organic group, and the atom bonded to Y is a carbon atom. 2 Examples of the monovalent organic group in include substituted or unsubstituted hydrocarbon groups (monovalent hydrocarbon groups), substituted or unsubstituted heterocyclic groups (monovalent heterocyclic groups), and groups in which two or more of the above monovalent hydrocarbon groups and / or monovalent heterocyclic groups are bonded. The bonded groups may be bonded directly or via a linking group. Examples of the linking group include amino groups, ether bonds, ester bonds, phosphinic acid groups, sulfide bonds, carbonyl groups, amide groups, urethane bonds, imide bonds, thiocarbonyl groups, siloxane bonds, and groups in which two or more of these are bonded.

[0099] Examples of the hydrocarbon group in the monovalent organic group include an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, an aromatic hydrocarbon group, and groups in which two or more of these are bonded together.

[0100] Examples of the aliphatic hydrocarbon group include an alkyl group, an alkenyl group, and an alkynyl group. Examples of the alkyl group include a C group such as a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, a hexyl group, an octyl group, an isooctyl group, a decyl group, and a dodecyl group. 1-22 Alkyl group (preferably C 2-20 Alkyl groups, more preferably C 3-18 Examples of the alkenyl group include C groups such as vinyl group, allyl group, methallyl group, 1-propenyl group, isopropenyl group, 1-butenyl group, 2-butenyl group, 3-butenyl group, 1-pentenyl group, 2-pentenyl group, 3-pentenyl group, 4-pentenyl group, and 5-hexenyl group. 2-22 Alkenyl group (preferably C 4-20 Alkenyl groups, more preferably C 8-18 Examples of the alkynyl group include C alkynyl groups such as ethynyl and propynyl groups. 2-22 Alkynyl groups (preferably C 4-20 Alkynyl groups, more preferably C 8-18 alkynyl groups).

[0101] Examples of the alicyclic hydrocarbon group include C cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, and cyclododecyl groups. 3-12 Cycloalkyl groups; cyclohexenyl groups, etc. 3-12 Cycloalkenyl groups; bicycloheptanyl groups, bicycloheptenyl groups, etc. 4-15 and bridged cyclic hydrocarbon groups.

[0102] Examples of the aromatic hydrocarbon group include C phenyl groups, naphthyl groups, etc. 6-14 Aryl groups (especially C 6-10 Aryl groups).

[0103] The heterocyclic ring forming the heterocyclic group includes R 1 Examples of the monovalent organic group in the above formula include those exemplified and explained above.

[0104] Examples of the group in which two or more of the monovalent hydrocarbon groups and / or monovalent heterocyclic groups are bonded via a linking group include a group in which the monovalent hydrocarbon group and / or the monovalent heterocyclic group is bonded to an alkoxy group, an alkenyloxy group, an alkynyloxy group, an aryloxy group, an aralkyloxy group, an acyloxy group, an alkylthio group, an alkenylthio group, an arylthio group, an aralkylthio group, an acyl group, an alkenylcarbonyl group, an arylcarbonyl group, an aralkylcarbonyl group, an alkoxycarbonyl group, an alkenyloxycarbonyl group, an aryloxycarbonyl group, an aralkyloxycarbonyl group, a dialkylamino group, an acylamino group, an oxetanyl group-containing group, a carbamoyl group, an epoxy group-containing group such as a glycidyloxy group, or a group in which two or more of these are bonded to each other.

[0105] The hydrocarbon group in the monovalent organic group may have a substituent. Examples of the substituent include halogen atoms such as fluorine, chlorine, bromine, and iodine atoms; cyano groups; isocyanate groups; and isothiocyanate groups. However, it is preferable that the monovalent organic group does not have a hydroxy group, a carboxy group, an amino group, a mono-substituted amino group, a terminal alkenyl group, or a terminal epoxy group (particularly, a functional group containing active hydrogen) as a substituent other than -YH.

[0106] Above R 2It is preferable that the hydrocarbon group contains a linear hydrocarbon group having 4 or more consecutive carbon atoms. Examples of such a hydrocarbon group include linear alkylene groups such as tetramethylene, pentamethylene, hexamethylene, heptamethylene, octamethylene, nonamethylene, and decamethylene groups; branched alkylene groups such as 2-ethylhexamethylene groups; linear alkenylene groups such as 1-butenylene, 2-butenylene, 1-pentenylene, 2-pentenylene, and 3-pentenylene groups; branched alkenylene groups such as 2-methyl-2-butenylene groups; alicyclic hydrocarbon groups having 4 or more carbon atoms such as cyclohexyl groups; aromatic hydrocarbon groups having 6 or more carbon atoms such as phenyl groups; and heterocyclic groups containing a structure having 4 or more consecutive carbon atoms such as piperidine rings.

[0107] In formula (2), the molar ratio of carbon atoms to the total amount of heteroatoms selected from the group consisting of nitrogen atoms, oxygen atoms, sulfur atoms, and silicon atoms is preferably 4.5 or more, more preferably 5 or more, and even more preferably 5.5 or more. When the molar ratio is 4.5 or more, the obtained surface-modified ND particles have excellent dispersibility in an organic dispersion medium as a lubricant base. The molar ratio may be 22 or less, or may be 20 or less.

[0108] In formula (2), the number of carbon atoms is preferably 6 to 22, and more preferably 8 to 20. When the number of carbon atoms is 6 or more, the steric hindrance between the surface modification groups is sufficient, and the surface modification groups are easily dispersed in the organic dispersion medium as the lubricant base. When the number of carbon atoms is 22 or less, the surface modification groups are prevented from becoming entangled with each other, and the surface modification groups are easily dispersed in the organic dispersion medium as the lubricant base.

[0109] Among the above-mentioned monovalent organic groups, preferred are monovalent substituted or unsubstituted hydrocarbon groups, groups in which a monovalent substituted or unsubstituted hydrocarbon group is bonded to an alkoxy group, and groups in which a monovalent substituted or unsubstituted hydrocarbon group is bonded to a dialkylamino group.

[0110] In particular, in the above formula (2), Y is preferably -O-, -C(=O)-O-, or -NH-. When Y is -O- or -C(=O)-O-, R 2 is preferably a monovalent substituted or unsubstituted hydrocarbon group, and more preferably a linear or branched hydrocarbon group having 8 to 20 carbon atoms.

[0111] When Y is -NH-, R 2 is preferably a monovalent organic group containing 8 to 20 carbon atoms. 2 is preferably a monovalent organic group containing a hydrocarbon group having four or more consecutive carbon atoms in a straight chain.

[0112] The above reaction step is carried out in a state where the ND particles are nano-dispersed in water, i.e., in an aqueous dispersion composition of ND particles. The median diameter (D50) of the ND particles in the aqueous dispersion composition is preferably 1 to 100 nm, more preferably 1 to 50 nm, and even more preferably 1 to 10 nm. When the median diameter is within the above range, the amount of hydroxyl groups and / or carboxyl groups on the ND particle surface is large, and the reaction with the compound represented by formula (2) proceeds more. In addition, the dispersibility of the obtained surface-modified ND particles is excellent.

[0113] The acid catalyst may be a known or conventional acid catalyst used in the esterification of carboxylic acid and alcohol, the dehydration condensation reaction of alcohol and amine, the dehydration condensation reaction of alcohol and thiol, etc. Examples of the acid catalyst include a sulfonic acid group-containing compound, hydrochloric acid, nitric acid, sulfuric acid, sulfuric anhydride, phosphoric acid, boric acid, trihaloacetic acid (trichloroacetic acid, trifluoroacetic acid, etc.), their salts (ammonium salts, etc.), inorganic solid acids, etc. The acid catalyst may be used alone or in combination of two or more.

[0114] The acid catalyst may be in the form of either a homogeneous catalyst that can be dissolved in a solvent or a substrate during the reaction, or a heterogeneous catalyst that cannot be dissolved during the reaction. Examples of heterogeneous catalysts include supported catalysts in which an acid component is supported on a carrier.

[0115] Examples of the sulfonic acid group-containing compound include aliphatic sulfonic acids such as methanesulfonic acid, ethanesulfonic acid, propanesulfonic acid, butanesulfonic acid, dodecanesulfonic acid, hexadecanesulfonic acid, trifluoromethanesulfonic acid, and heptadecafluorooctanesulfonic acid; alicyclic sulfonic acids such as 10-camphorsulfonic acid; benzenesulfonic acid, p-toluenesulfonic acid, 2,4,6-trimethylbenzenesulfonic acid, hexylbenzenesulfonic acid, and octylbenzenesulfonic acid. aromatic sulfonic acids such as sulfonic acid, decylbenzenesulfonic acid, dodecylbenzenesulfonic acid (DBSA), octadecylbenzenesulfonic acid, 1-naphthalenesulfonic acid, 2-naphthalenesulfonic acid, and butyl-2-naphthalenesulfonic acid; sulfonic acid-type ion exchange resins, 3-[trioctylammonio]propane-1-sulfonic acid-triflimide, 4-[trioctylammonio]butane-1-sulfonic acid-triflimide, and compounds represented by the following formula (A).

[0116] [ka]

[0117] Examples of the inorganic solid acid include silica, silica alumina, alumina, zeolites, activated clay, and montmorillonite.

[0118] Examples of the ammonium salt as the acid catalyst include an ammonium ion salt represented by the following formula (B-1), an ammonium ion salt represented by the following formula (B-2), an ammonium ion salt represented by the following formula (B-3), and an ammonium ion salt represented by the following formula (B-4). [ka]

[0119] In the above formula (B-1), R I ~R IIIare the same or different and each represents a group containing a hydrogen atom, an aliphatic hydrocarbon group, or an aromatic hydrocarbon group. The aliphatic hydrocarbon group is a linear or branched C 1-22 Hydrocarbon groups are preferred. Examples of the group containing an aromatic hydrocarbon group include aromatic hydrocarbon groups such as a phenyl group; and groups in which an aliphatic hydrocarbon group and an aromatic hydrocarbon group are bonded, such as a 4-t-butylphenyl group and a mesityl group. Among these, the above R I ~R III It is preferable that two or more of the above groups contain an aromatic hydrocarbon group.

[0120] The acid anion serving as a counter anion to the ammonium ions represented by the above formulas (B-1) to (B-3) is preferably a sulfonate ion, more preferably an aromatic sulfonate ion, and particularly preferably a p-dodecylbenzenesulfonate ion.

[0121] In the above formula (B-4), R i and R ii are the same or different and each represents a group containing a hydrogen atom, an aliphatic hydrocarbon group, or an aromatic hydrocarbon group. The aliphatic hydrocarbon group is a linear or branched C 1-4 Hydrocarbon groups are preferred. Examples of the group containing an aromatic hydrocarbon group include aromatic hydrocarbon groups such as a phenyl group, and groups in which an aliphatic hydrocarbon group and an aromatic hydrocarbon group are bonded. Among these, a hydrogen atom, a methyl group, an isopropyl group, and a phenyl group are preferred.

[0122] The acid anion serving as a counter anion to the ammonium ion represented by the above formula (B-4) is preferably a sulfonate ion or a sulfate ion, and particularly preferably a trifluoromethanesulfonate ion, a 10-camphorsulfonate ion, a benzenesulfonate ion, or a sulfate ion.

[0123] The acid anion serving as the counter anion of the ammonium ion represented by the above formulae (B-1) to (B-4) may form a complex salt by forming a hydrogen bond between an oxygen atom forming an acid group and a hydrogen atom on a nitrogen atom in the above formulae (B-1) to (B-4). The above complex salt may form one salt with one ammonium cation and one acid anion, or may form one salt with two ammonium cations and two acid anions, and the number of ammonium cations and acid anions forming one salt is not particularly limited. In one salt, the acid anion may form a polymer. For example, sulfuric acid forming a sulfate ion is [H2SO4(SO3) X An example of the complex salt formed between the acid anion and the above formula (B-4) is a compound represented by the following formula (C). [ka]

[0124] In the above formula (C), R i and R ii is the same as in the above formula (B-4).

[0125] As the acid catalyst, from the viewpoint of further accelerating the reaction in the reaction step, a sulfonic acid group-containing compound or an ammonium salt of a sulfonic acid group-containing compound is preferred.

[0126] The ratio (former:latter, mass ratio) of the ND particles to be reacted to the compound represented by the above formula (2) is, for example, 1:1 to 1:25. The concentration of the ND particles in the water-dispersed composition is, for example, 1 to 10 mass%, and the concentration of the compound represented by the above formula (2) in the water-dispersed composition is, for example, 1 to 60 mass%.

[0127] The reaction conditions for the ND particles and the compound represented by the above formula (2) can be appropriately selected within the ranges of, for example, a temperature of 0 to 100° C., a reaction time of 1 to 48 hours, and a pressure of 1 to 5 atm.

[0128] The content of the ND particles in the lubricant composition (Y) is, for example, 0.01 to 5.0 mass%, preferably 0.1 to 4.0 mass%, more preferably 0.25 to 3.0 mass%, and even more preferably 0.5 to 2.0 mass%. The content of the ND particles in the lubricant composition (Y) may be, for example, 0.1 to 2000 mass ppm, preferably 0.2 to 1000 mass ppm, more preferably 0.5 to 500 mass ppm, and even more preferably 1.0 to 100 mass ppm. Since the lubricant composition (Y) has excellent dispersibility of the ND particles, even with such a two-stage content ratio, the dispersibility in the organic dispersion medium as the lubricant base is excellent. For this reason, the content of the ND particles in the lubricant composition (Y) can be different between when it is distributed and when it is used, for example, 0.01 to 5.0 mass% during distribution and 0.1 to 2000 mass ppm during use. In addition, when the content is 0.1 to 2000 ppm by mass, the effects of reducing the friction coefficient in the boundary lubrication region, suppressing seizure of the sliding member, reducing the amount of wear of the sliding member, and expanding the mixed lubrication region and the hydrodynamic lubrication region are more excellent. The content of the ND particles can be calculated from the absorbance at 350 nm.

[0129] The content of the solvent in the lubricant composition (Y) is, for example, 90 to 99.9999% by mass, and the content of the organic dispersion medium as a lubricant base in the total amount of the solvent is, for example, 60% by mass or more, preferably 70% by mass or more, more preferably 80% by mass or more, and particularly preferably 90% by mass or more.

[0130] When the content of ND particles in the lubricant composition (Y) is 0.01 to 5.0 mass%, the average dispersed particle size (D50) of the ND particles in the lubricant composition (Y) is preferably 2 to 50 nm, more preferably 4 to 30 nm, further preferably 6 to 25 nm, and particularly preferably 10 to 20 nm.

[0131] When the content of ND particles in the lubricant composition (Y) is 0.1 to 2000 ppm by mass, the average dispersed particle size (D50) of the ND particles in the lubricant composition is preferably 5 to 100 nm, more preferably 8 to 80 nm, even more preferably 10 to 60 nm, still more preferably 15 to 40 nm, and particularly preferably 18 to 35 nm.

[0132] The lubricant composition (Y) preferably has a haze value of 5 or less, more preferably 3 or less, and even more preferably 1 or less. The lubricant composition (Y) has excellent dispersibility of ND particles, so that a lubricant composition having the above haze value can be obtained. The above haze value can be measured based on JIS K 7136.

[0133] The lubricant composition (Y) may be composed of only the above ND particles and lubricant base, or may contain other components. Examples of other components include surfactants, thickeners, coupling agents, dispersants, rust inhibitors, corrosion inhibitors, freezing point depressants, antifoaming agents, antiwear additives, preservatives, and colorants. The content ratio of the above other components is, for example, 30% by mass or less, preferably 20% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, and particularly preferably 1% by mass or less, based on the total amount of the lubricant composition (Y). Therefore, the total content ratio of the ND particles and the lubricant base is, for example, 70% by mass or more, preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and particularly preferably 99% by mass or more, based on the total amount of the lubricant composition (Y).

[0134] The lubricant composition (Y) can be produced, for example, by mixing and dispersing the above-mentioned surface-modified ND particles and, if necessary, other components in an organic dispersion medium as a lubricant base. After obtaining the above-mentioned water-dispersed composition of surface-modified ND, before or after distilling off the water in the dispersion composition with an evaporator or the like, the lubricant composition (Y) can also be produced by mixing and stirring a new dispersion medium, i.e., by exchanging the solvent.

[0135] When obtaining the lubricant composition (Y) by exchanging the solvent, it is preferable to add an organic dispersion medium having excellent dispersibility of the surface-modified ND at one end, remove water by extraction and / or distillation to exchange the solvent, and then add a new lubricant base. It is also possible to add a new lubricant base and remove water by extraction and / or distillation to exchange the solvent without adding an organic dispersion medium having excellent dispersibility of the surface-modified ND. In addition, washing with water and / or saline may be performed before removing water. The lubricant base is appropriately selected from the lubricant base materials used in the lubricant composition (Y) described above. The lubricant base may be used alone or in combination of two or more.

[0136] The lubricant composition (Y) can impart excellent wear-inhibiting and friction-reducing effects to sliding members, and the excellent wear-inhibiting and friction-reducing effects can prevent or suppress seizure of the sliding members.

[0137] [Method of manufacturing carbon transfer film and sliding member] The carbon transfer film (X) and the sliding member can be produced by sliding the sliding surface of the substrate and the sliding surface of the sliding member relative to each other in the presence of a lubricant composition (e.g., lubricant composition (A)) in which nanodiamond particles are nano-dispersed and the zirconia content is less than 100 mass ppm. It is presumed that the carbon transfer film (X) is formed by the sliding, by which carbon derived from the nanodiamond particles in the lubricant composition is transferred onto the substrate, and further, in some cases, the components in the substrate and / or the sliding member are also transferred onto the substrate.

[0138] An embodiment of the method for producing the carbon transfer film (X) and the sliding member will be specifically described with reference to Fig. 2. As shown in Fig. 2(a), in the above-mentioned production method, first, a lubricant composition (lubricant composition (A)) 13 in which ND particles are nano-dispersed and the content of zirconia is less than 100 mass ppm is dropped onto a substrate 11. Then, a sliding member 14 is placed on the substrate 11 in the area where the lubricant composition 13 has spread. The order of applying the lubricant composition 13 and placing the sliding member 14 may be reversed.

[0139] 2, the sliding member 14 is a sphere and the substrate 11 is a disk, but the shapes and dimensions of the sliding member and the substrate are not particularly limited and may be appropriately configured from various shapes and dimensions depending on the application, etc. In addition, the hardness of the substrate and the sliding member may be different or the same.

[0140] The sliding member is for forming a carbon transfer film (X) by sliding with the sliding surface of the substrate. Examples of the sliding member include alloy steels such as carbon steel, chromium steel, and chromium molybdenum steel, alloy tool steel, stainless steel (e.g., SUS), bearing steel (e.g., SUJ), and spring steel (e.g., SUP), as well as metal materials such as copper plate, aluminum plate, and titanium plate. The surface of the sliding member may be provided with a carbon film such as a diamond-like carbon (DLC) film. The surface of the sliding member may be subjected to various surface treatments such as various electrochemical treatments such as plating, chemical conversion treatment, and anodization; various coatings such as flow coating and powder coating; and physical surface treatments such as shot blasting.

[0141] Next, as shown in FIG. 2(b), the sliding surface of the substrate 11 and the sliding surface of the sliding member 14 are relatively slid in the presence of the lubricant composition 13. At this time, the lubricant composition 13 is interposed between the substrate 11 and the sliding member 14. When the substrate 11 and the sliding member 14 are relatively slid, the ND particles (not shown) contained in the lubricant composition 13 form a local high energy field at the friction part due to the pressure contact sliding between the substrate 11 and the sliding member 14, which is considered to promote the reaction and transfer the carbon derived from the ND particles to the surface of the substrate 11. Furthermore, there are cases where components derived from the substrate 11 and / or the sliding member 14 are also transferred to the substrate 11.

[0142] The sliding is not particularly limited, and may be a reciprocating motion or a circumferential sliding. The sliding may be performed by known or conventional sliding such as ball (pin) on disk rotation type, ball (pin) on disk reciprocating motion, thrust cylinder type, block on ring type, four ball type, pin block type, vibration friction wear, etc.

[0143] In the illustrated example, a low-friction surface is formed on the surface of the substrate 11. A coating containing a large amount of oxygen is formed on the low-friction surface. This is believed to be due to the formation of a coating having a low-friction surface by a tribochemical reaction in a system in which ND particles are present.

[0144] As shown in FIG. 2(c), the friction caused by the pressure-contact sliding between the substrate 11 and the sliding member 14 causes the ND particles (not shown) contained in the lubricant composition 13 to form a carbon transfer film (X) 12 on the surface of the substrate 11. In addition, a carbon transfer film 12 may also be formed on the surface of the sliding member 14 by the same principle. The carbon transfer film 12 is formed by sliding in the presence of a lubricant composition with a low zirconia content, so that the transfer of zirconium derived from zirconia is suppressed, resulting in a low zirconium content. Note that in FIG. 2, the substrate 11 and the sliding member 14 may be reversed, i.e., the substrate 11 may be a sphere and the sliding member 14 may be a disk.

[0145] The sliding may be performed under boundary lubrication conditions. The carbon transfer film (X) and the method for producing the sliding member can produce a carbon transfer film and a sliding member having the carbon transfer film formed thereon, which have excellent friction reduction and wear suppression effects, even under the extremely severe conditions of boundary lubrication conditions. In this specification, the term "under boundary lubrication conditions" refers to performing the sliding in the above-mentioned boundary lubrication region.

[0146] In the manner described above, the carbon transfer film (X) and the sliding member can be manufactured. The carbon transfer film (X) and the sliding member obtained in this manner have excellent friction reducing and wear suppressing effects. Therefore, it is possible to reduce the friction and wear of the carbon transfer film itself, and also to simultaneously reduce the friction and wear of the sliding counter member. This makes it possible to prevent or suppress seizure of the sliding member.

[0147] Each aspect disclosed in this specification can be combined with any other feature disclosed in this specification. Each configuration in each embodiment and their combinations are merely examples, and addition, omission, substitution, and other modifications of the configuration are possible as appropriate within the scope of the present disclosure. In addition, each invention according to this disclosure is not limited by the embodiments or the following examples, but is limited only by the claims. EXAMPLES

[0148] The present disclosure will be described in more detail below based on examples, but the present disclosure is not limited to these examples.

[0149] Example 1 The surface-modified ND particles, the lubricant composition, the transfer film, and the sliding member were produced through the following steps.

[0150] (Preparation of surface-modified ND particles and lubricant composition) First, the process of generating ND by detonation was carried out. In this process, the formed explosive with an electric detonator was placed inside a pressure-resistant container for detonation and the container was sealed. The container was made of iron and had a volume of 15 m. 3 As the explosive, 0.50 kg of a mixture of TNT and RDX was used. The mass ratio of TNT and RDX in this explosive (TNT / RDX) was 50 / 50. Next, an electric detonator was detonated to detonate the explosive in the container (production of ND by the detonation method). Next, the container and its inside were allowed to cool by leaving it at room temperature for 24 hours. After this cooling, the ND crude product (including the aggregated body of ND particles and soot generated by the above-mentioned detonation method) adhering to the inner wall of the container was scraped off with a spatula, and the ND crude product was collected.

[0151] Next, an oxidation treatment step was performed. The ND crude product obtained by performing the above-mentioned generation step multiple times was subjected to the oxidation treatment step. Specifically, 6 L of 98% by mass sulfuric acid and 1 L of 69% by mass nitric acid were added to the obtained ND crude product to form a slurry, and the slurry was then subjected to a heat treatment for 48 hours under reflux under normal pressure conditions. The heating temperature in this oxidation treatment was 140 to 160°C. Next, after cooling, the solid content (including the ND aggregate) was washed with water by decantation. The supernatant liquid at the beginning of the washing was colored, and the solid content was repeatedly washed with water by decantation until the supernatant liquid became transparent to the naked eye. After that, it was dried to obtain the ND aggregate as a powder. Furthermore, it was heated at 400°C for 6 hours in a rotary kiln into which a gas of about 8% by volume of oxygen and about 92% by volume of nitrogen was blown at a flow rate of 20 L / min.

[0152] Next, about 30 ml of the slurry containing the ND aggregates obtained through the above-mentioned oxidation treatment process was adjusted to pH 10 using ammonia water, and then bead milling was performed using a bead milling device (product name "Parallel Four-Cylinder Sand Grinder LSG-4U-2L Type", manufactured by IMEX Co., Ltd.). Specifically, 30 ml of the slurry after ultrasonic irradiation and zirconia beads with a diameter of 30 μm were charged and sealed in a 100 ml milling vessel (manufactured by IMEX Co., Ltd.), and the device was driven to perform bead milling. In this bead milling, the amount of zirconia beads charged was, for example, 33 volume % with respect to the volume of the milling vessel, the rotation speed of the milling vessel was 2570 rpm, and the milling time was 3 hours.

[0153] Next, the slurry that had undergone the above-mentioned disintegration process was centrifuged using a centrifuge (classification operation). The centrifugal force in this centrifugation process was 20,000×g, and the centrifugation time was 30 minutes. Next, 10 ml of the supernatant of the ND-containing solution that had undergone the above-mentioned centrifugation process was collected. In this way, an ND aqueous dispersion in which nanodiamonds were dispersed in pure water was obtained. The solid content of this ND aqueous dispersion was 6.0 mass %, and the pH was 9.0. The median diameter (particle size D50) of the ND aqueous dispersion obtained as described above was 6.0 nm.

[0154] Next, 0.5 mmol of dodecylbenzenesulfonic acid and 2 mmol of n-octadecanol were added as an acid catalyst to 1 g of the ND aqueous dispersion obtained through the above-mentioned disintegration process, and the mixture was reacted at 80° C. for 8 hours while stirring. After the reaction was completed, the reaction residue and the acid catalyst were removed, and the solvent was replaced with toluene to obtain a surface-modified ND toluene dispersion. The median diameter (particle size D50) of the surface-modified ND particles in the obtained surface-modified ND toluene dispersion was about 18 nm, and the mass ratio [ND / surface-modifying group] determined by thermogravimetric analysis was 14.6. 10 mL of lubricating oil (trade name "Mobil Velocite Oil No. 10", manufactured by Exxon Mobil Corporation) was added to this surface-modified ND toluene dispersion to obtain a lubricant composition in which ND particles modified with n-octadecaneoxy groups were nano-dispersed.

[0155] (Preparation of transfer film) The lubricant composition was diluted with the lubricating oil to a surface-modified ND particle concentration of 500 mass ppm, which was used as the lubricant composition for forming the transfer film. The transfer film was formed using an SRV friction tester (device name "The basic SRV5 oscillation system", manufactured by Optimol). As the ball and disk in the SRV friction tester, a ball made of SUJ2 with a diameter of 10 mm and a disk made of SUJ2 with a diameter of 24 mm and a thickness of 7.85 mm were used, both of which were subjected to mirror polishing (Ra = 25 nm or less) after quenching. When the ball and disk started to slide, 10 μL of the lubricant composition was dropped on the sliding surface of the disk surface, and the test was performed at room temperature. The conditions for forming the transfer film were an initial load of 100 N, an amplitude of 1.5 mm, a frequency of 50 Hz, and a time of 20 minutes. Thereafter, the ball and disk were removed from the friction tester and washed with hexane and acetone to remove the lubricant composition. In this manner, a transfer film was formed on the surface of the SUJ2 substrate, which was a disk, to obtain a transfer film and a sliding member of Example 1.

[0156] Example 2 A transfer film and a sliding member of Example 2 were obtained by forming a transfer film in the same manner as in Example 1, except that the concentration of the surface-modified ND particles in the lubricant composition for forming the transfer film was 100 ppm by mass.

[0157] Comparative Example 1 (Preparation of surface-modified ND particles) First, the process of generating ND by detonation was carried out. In this process, the formed explosive with an electric detonator was placed inside a pressure-resistant container for detonation and the container was sealed. The container was made of iron and had a volume of 15 m. 3As the explosive, 0.50 kg of a mixture of TNT and RDX was used. The mass ratio of TNT and RDX in this explosive (TNT / RDX) was 50 / 50. Next, an electric detonator was detonated to detonate the explosive in the container (production of nanodiamonds by the detonation method). Next, the container and its inside were allowed to cool by leaving it at room temperature for 24 hours. After this cooling, the ND crude product (including the aggregates of ND particles and soot produced by the above-mentioned detonation method) adhering to the inner wall of the container was scraped off with a spatula, and the ND crude product was collected.

[0158] The ND crude product obtained by carrying out the above-mentioned production process multiple times was then subjected to an acid treatment process. Specifically, 6 L of 10 mass % hydrochloric acid was added to 200 g of the ND crude product to obtain a slurry, which was then subjected to a heat treatment under reflux at normal pressure for 1 hour. The heating temperature in this acid treatment was 85 to 100°C. Next, after cooling, the solid matter (including ND aggregates and soot) was washed with water by decantation. The solid matter was repeatedly washed with water by decantation until the pH of the precipitation liquid reached 2 from the low pH side.

[0159] Next, an oxidation treatment step was performed. Specifically, 6 L of 98% by mass sulfuric acid and 1 L of 69% by mass nitric acid were added to the precipitate liquid (containing ND aggregates) obtained through decantation after the acid treatment to form a slurry, and the slurry was then subjected to a heat treatment for 48 hours under reflux at normal pressure. The heating temperature in this oxidation treatment was 140 to 160°C. Next, after cooling, the solid matter (containing ND aggregates) was washed with water by decantation. The supernatant liquid at the beginning of the washing was colored, and the solid matter was repeatedly washed with water by decantation until the supernatant liquid became visually transparent.

[0160] Next, 1000 mL of the ND-containing solution obtained through the above-mentioned water washing treatment was spray-dried using a spray drying device (product name "Spray Dryer B-290", manufactured by Nippon Buchi Co., Ltd.) (drying step). As a result, 50 g of ND powder was obtained.

[0161] 3.0 g of the ND particles obtained in the above drying step was weighed out and placed in a reaction vessel, and 150 g of toluene as an organic dispersion medium and 12.0 g of hexadecyltrimethoxysilane as a silane compound were added and stirred for 10 minutes.

[0162] After stirring, 360 g of zirconia beads (manufactured by Tosoh Corporation, registered trademark "YTZ", diameter 30 μm) were added. After the addition, the mixture was cooled in ice water and ultrasonicated for 20 hours using an ultrasonic disperser (model "UP-400s", manufactured by Hielscher) with the tip of the ultrasonic disperser's vibrator immersed in the solution in the reaction vessel, to react the ND particles with the silane compound. The liquid was initially gray, but the particle size gradually became smaller and the dispersion state improved, and finally it became a uniform black liquid. This is thought to be because the ND particles were successively disintegrated (disintegrated) from the ND particle aggregates, the silane compound acted on the ND particles in the dissociated state and bonded to them, and the surface-modified ND particles were dispersed and stabilized in toluene. In this way, a surface-modified ND dispersion (toluene dispersion) in which surface-modified ND particles with silane compounds bonded to the surface were nano-dispersed was obtained. The particle size distribution of the ND particles in the obtained ND dispersion was measured by dynamic light scattering (non-contact backscattering method) using a Malvern device (product name "Zetasizer Nano ZS"), and the average dispersed particle diameter (D50) of the ND particles was calculated to be 12 nm.

[0163] Next, 10 mL of lubricating oil (product name "Mobil Velocite Oil No. 10", ExxonMobil) was added to the toluene dispersion obtained through the above-mentioned disintegration process, and then the mixture was stirred and dispersed. In this manner, a lubricant composition in which surface-modified ND particles having a silane compound bonded to the surface were nano-dispersed was obtained.

[0164] (Preparation of transfer film) The lubricant composition was diluted with the lubricating oil to a surface-modified ND particle concentration of 500 ppm by mass to prepare a lubricant composition for forming a transfer film. The zirconia concentration in the lubricant composition was 950 ppm by mass.

[0165] A transfer film was formed in the same manner as in Example 1, except that the lubricant composition obtained above was used as the lubricant composition for forming the transfer film, and a transfer film and a sliding member of Comparative Example 1 were obtained.

[0166] Comparative Example 2 A transfer film and a sliding member of Comparative Example 2 were obtained by forming a transfer film in the same manner as in Comparative Example 1, except that the concentration of the surface-modified ND particles in the lubricant composition for forming the transfer film was 100 mass ppm.

[0167] (evaluation) The transfer films and sliding members produced in Examples 1 and 2 and Comparative Examples 1 and 2 were evaluated as follows.

[0168] (1) Evaluation of low friction effect In Example 2 and Comparative Example 2, the change in friction coefficient from the start to the end of the transfer film formation was measured to evaluate the low-friction effect. That is, the change in the friction reduction effect during the process of obtaining a sliding member on which a transfer film was formed was evaluated. The results of Example 2 are shown in FIG. 3, and the results of Comparative Example 2 are shown in FIG. 4.

[0169] (2) Wear cross-sectional area measurement For the disks in the sliding members obtained in Example 2 and Comparative Example 2, the wear area was scanned with a double-scan high-precision laser measuring device (product name "LT-9000", manufactured by Keyence Corporation), and the cross-sectional profile of any point was obtained to measure the wear cross-sectional area (N number = 3). As a result, the average value of the wear cross-sectional area at N3 was 137 μm 2 , Comparative Example 2 is 295 μm 2 Regarding the obtained cross-sectional profiles, the results of Example 2 and Comparative Example 2 are shown in FIG.

[0170] (3)SEM-EDX measurement The surfaces of the transfer films obtained in the examples and comparative examples were measured using a scanning electron microscope (SEM) (product name "SU5000", manufactured by Hitachi High-Technologies Corporation) and an energy dispersive X-ray spectrometer (product name "X-Max50", manufactured by OXFORD instruments) at an acceleration voltage of 5 kV, and the proportion of zirconium was calculated. As a result, no zirconium was detected in Examples 1 and 2, 5.7 mass% in Comparative Example 1, and 0.7 mass% in Comparative Example 2.

[0171] Example 3 The lubricant composition for forming the transfer film prepared in Example 1 was used to form the transfer film as follows. A ball-on-disk type sliding friction tester (apparatus name "UMT-3", manufactured by Bruker) was used to form the transfer film. As the ball and disk in the friction tester, a ball made of SUJ2 with a diameter of 4 mm and a disk made of SUJ2 were used, both of which were subjected to mirror polishing (Ra = 25 nm or less) after quenching. A silicon substrate was fixed with resin on the sliding surface of the SUJ2 disk, and the ball and the silicon substrate surface of the disk were slid. When the ball and disk started to slide, 10 μL of the lubricant composition for forming the transfer film was dropped on the sliding surface of the silicon substrate surface, and the test was performed at room temperature. The conditions for forming the transfer film were a rotation radius of 4 mm, a rotation speed of 100 rpm (circumferential speed of 42 mm / s), a load of 4.9 N, a heating stage setting temperature of 50 ° C, and a rotation time of 10 minutes. Thereafter, the ball and the disk were removed from the friction tester and washed with hexane and acetone to remove the lubricant composition, thus obtaining a transfer film and a sliding member of Example 3.

[0172] Example 4 A transfer film was formed in the same manner as in Example 3, except that the lubricant composition for forming a transfer film prepared in Example 2 was used as the lubricant composition for forming a transfer film, and a transfer film and a sliding member of Example 3 were obtained.

[0173] Comparative Example 3 A transfer film was formed in the same manner as in Example 3, except that the lubricant composition for forming a transfer film prepared in Comparative Example 1 was used as the lubricant composition for forming a transfer film, and a transfer film and a sliding member of Comparative Example 3 were obtained.

[0174] Comparative Example 4 A transfer film was formed in the same manner as in Example 3, except that the lubricant composition for forming a transfer film prepared in Comparative Example 2 was used as the lubricant composition for forming a transfer film, and a transfer film and a sliding member of Comparative Example 4 were obtained.

[0175] (evaluation) The transfer films and sliding members prepared in Examples 3-4 and Comparative Examples 3-4 were evaluated as follows. The Raman spectroscopic analysis and film thickness measurement were performed on the transfer film formed on the silicon substrate. This is because a more uniform transfer film can be obtained by forming the transfer film on a silicon substrate with a smooth surface, and thus Raman spectroscopic analysis and film thickness measurement can be performed easily. The carbon transfer film does not react with either silicon or iron, so the Raman spectroscopic analysis results and film thickness of the transfer film formed are not affected by the difference in the material of the substrate.

[0176] (3) Raman spectroscopy The surfaces of the transfer films obtained in the examples and comparative examples were irradiated under the following measurement conditions using a microscopic laser Raman spectrometer (product name "LabRAM HR Evolution", manufactured by Horiba, Ltd.). As a result, in all examples and comparative examples, sp 2 Carbon with bond and sp 3 It was determined that the carbon transfer film contained carbon having bonds. The Raman spectrum of Example 4 obtained is shown in FIG. 7. In the Raman spectrum of the carbon transfer film of Example 4, -1 sp 3 The peak of the carbon having a bond is 1390 cm -1 and 1542 cm -1 The D band peak is at 1606 cm -1 The sp band peaks of the carbon transfer film of Example 4 were observed. 2 Carbon with bond and sp 3 sp for the sum of carbons with bonds 3 The ratio of carbons with bonds sp 3 / (sp2 +sp 3 ) was confirmed to be 0.096. Measurement light source: 325nm Output power: 1.075mW Exposure time: 10 seconds Number of times: 4

[0177] (4) Film thickness measurement The thickness of the transfer film formed in Example 4 was measured at the 5-minute and 10-minute rotation times. The film thickness was measured by laser microscope observation. As a result, the film thickness of the transfer film at the 5-minute rotation time stage was 5 nm, and the film thickness of the transfer film at the 10-minute rotation time stage was 18 nm.

[0178] The transfer film obtained in Example 2 was sp 2 The film contained carbon having bonds, had a thickness of 18 nm, and no zirconium was detected by elemental analysis using SEM-EDX measurement of the surface, so that the zirconium content was determined to be 0.6 mass% or less. As shown in FIG. 3, the transfer film of Example 2 had a low and stable friction coefficient of about 0.13 to 0.15 from the initial stage of formation (i.e., at the start of sliding). The wear step area was 137 μm 2 On the other hand, the transfer film obtained in Comparative Example 2 had a thickness of 13 nm, and the proportion of zirconium calculated from elemental analysis by SEM-EDX measurement of the surface was determined to be 0.7 mass %. As shown in FIG. 4, the transfer film of Comparative Example 2 was seized at the initial stage of formation (i.e., at the start of sliding), and the friction coefficient increased. The friction coefficient began to stabilize about 500 seconds after the start of sliding, and the friction coefficient at this stage was about 0.16 to 0.18. The wear step area was 295 μm 2 From these results, compared to the transfer film of Comparative Example 2, the transfer film of Example 2 did not suffer from seizure in the initial stage of formation, was formed early, had a low friction coefficient, and further had a small wear cross-sectional area and a small amount of wear.

[0179] Variations of the invention according to the present disclosure are described below. [Appendix 1]sp 2A carbon transfer film containing carbon having bonds, a zirconium ratio calculated from elemental analysis by SEM-EDX measurement of the surface being 0.6 mass % or less, and a thickness of less than 100 nm. [Appendix 2] Furthermore, sp 3 2. The carbon transfer film of claim 1, comprising carbon having bonds. [Appendix 3] The above sp 3 3. The carbon transfer film of claim 2, wherein the carbon having bonds is carbon from diamond. [Appendix 4] See above sp 2 Carbon having a bond and the sp 3 The sp 3 The ratio of carbons with bonds sp 3 / (sp 2 +sp 3 4. The carbon transfer film of claim 2 or 3, wherein the n-th order is 0.2 or less (preferably 0.1 or less, more preferably less than 0.1). [Appendix 5] In the Raman spectrum obtained by Raman spectroscopy using a measurement light source of 325 nm, the peak intensity is 1570 to 1640 cm -1 (Preferably 1580-1640cm -1 , more preferably 1590 to 1630 cm -1 , more preferably 1600 to 1620 cm -1 ) and the G band observed in the 1300-1400 cm -1 5. The carbon transfer film according to any one of claims 2 to 4, having a D band observed in the range. [Appendix 6] See above sp 2 6. The carbon transfer film of any one of claims 1 to 5, wherein the carbon having bonds is carbon derived from diamond. [Appendix 7] A carbon transfer film according to any one of Appendices 1 to 6, in which the proportion of zirconium calculated by elemental analysis using SEM-EDX measurement of the surface is 0.6 mass% or less (preferably 0.3 mass% or less, more preferably 0.1 mass% or less, and even more preferably 500 mass ppm or less). [Appendix 8] The carbon transfer film according to any one of Appendices 1 to 7, having a surface friction coefficient of 0.2 or less (preferably 0.17 or less, more preferably 0.16 or less).

[0180] [Appendix 9] A substrate and a carbon transfer film provided on at least one surface of the substrate, the carbon transfer film being sp 2 A sliding member comprising carbon having bonds, having a thickness of less than 100 nm, and having a zirconium ratio of 0.6 mass % or less (preferably 0.3 mass % or less, more preferably 0.1 mass % or less, and even more preferably 500 mass ppm or less) calculated by elemental analysis by SEM-EDX measurement of the surface of the carbon transfer film. [Appendix 10] The sliding member according to appendix 9, wherein the carbon transfer film contains a component derived from the substrate. [Appendix 11] The sliding member according to appendix 9 or 10, wherein the carbon transfer film is the carbon transfer film according to any one of appendixes 1 to 8.

[0181] [Appendix 12] A lubricant composition comprising an organic dispersion medium as a lubricant base and nanodiamond particles nano-dispersed in the organic dispersion medium, the lubricant composition having a zirconia content of less than 100 ppm by mass (preferably 20 ppm by mass or less, more preferably 2 ppm by mass or less). [Appendix 13] A lubricant composition according to Appendix 12, wherein the nanodiamond particles are surface-modified nanodiamond particles having a surface modified with a group represented by the following formula (1): -XR 1 (1) [In formula (1), X represents -NH-, -O-, -OC(=O)-, -C(=O)-O-, -NH-C(=O)-, -C(=O)-NH-, or -S-, and the bond extending to the left from X is bonded to the nanodiamond particle. R 1 represents a monovalent organic group, and the atom bonded to X is a carbon atom. However, in formula (1), the molar ratio of carbon atoms to the total amount of heteroatoms selected from the group consisting of nitrogen atoms, oxygen atoms, sulfur atoms, and silicon atoms is 4.5 or more. [Appendix 14] A lubricant composition comprising an organic dispersion medium as a lubricant base and surface-modified nanodiamond particles nano-dispersed in the organic dispersion medium and surface-modified with a group represented by the following formula (1): -XR 1 (1) [In formula (1), X represents -NH-, -O-, -OC(=O)-, -C(=O)-O-, -NH-C(=O)-, -C(=O)-NH-, or -S-, and the bond extending to the left from X is bonded to the nanodiamond particle. R 1 represents a monovalent organic group, and the atom bonded to X is a carbon atom. However, in formula (1), the molar ratio of carbon atoms to the total amount of heteroatoms selected from the group consisting of nitrogen atoms, oxygen atoms, sulfur atoms, and silicon atoms is 4.5 or more. [Appendix 15] R 1 is a monovalent organic group that does not have a hydroxy group, a carboxy group, an amino group, a mono-substituted amino group, a terminal alkenyl group, or a terminal epoxy group. [Appendix 16] The lubricant composition according to Appendices 15, wherein the monovalent organic group is a monovalent substituted or unsubstituted hydrocarbon group, a group in which a monovalent substituted or unsubstituted hydrocarbon group is bonded to an alkoxy group, or a group in which a monovalent substituted or unsubstituted hydrocarbon group is bonded to a dialkylamino group. [Appendix 17] The lubricant composition according to any one of Appendices 13 to 16, wherein X is -O-, -OC(=O)-, -C(=O)-O-, or -NH-. [Appendix 18] X is -O-, -OC(=O)-, or -C(=O)-O-, and R 1 is a monovalent substituted or unsubstituted hydrocarbon group (particularly, a monovalent substituted or unsubstituted hydrocarbon group not having a hydroxy group, a carboxy group, an amino group, a mono-substituted amino group, a terminal alkenyl group, or a terminal epoxy group) (more preferably a linear or branched hydrocarbon group having 8 to 20 carbon atoms (particularly a linear or branched hydrocarbon group having 8 to 20 carbon atoms and not having a terminal alkenyl group)). [Appendix 19] X is -NH-, and R 1 is a monovalent organic group having 8 to 20 carbon atoms (in particular, a monovalent organic group having 8 to 20 carbon atoms and not having a hydroxy group, a carboxy group, an amino group, a mono-substituted amino group, a terminal alkenyl group, or a terminal epoxy group). [Appendix 20] X is -NH- and R 1 is a monovalent organic group containing a linear hydrocarbon group with four or more consecutive carbon atoms (particularly, a monovalent organic group containing a linear hydrocarbon group with four or more consecutive carbon atoms and not having a hydroxy group, a carboxy group, an amino group, a mono-substituted amino group, a terminal alkenyl group, or a terminal epoxy group). [Appendix 21] A lubricant composition according to any one of Appendices 13 to 20, wherein the mass ratio of ND to the group represented by the following formula (1) [ND / the surface modifying group] in the surface modified nanodiamond particles is 0.5 or more (preferably 2.5 or more). [Appendix 22] The lubricant composition according to Appendix 21, wherein the mass ratio is 15.0 or less (preferably 10.0 or less, more preferably 7.0 or less, and even more preferably 5.0 or less). [Appendix 23] A lubricant composition according to any one of Appendices 13 to 22, wherein the content of the surface-modified nanodiamond particles is 0.01 to 5.0 mass% (preferably 0.1 to 4.0 mass%, more preferably 0.25 to 3.0 mass%, and even more preferably 0.5 to 2.0 mass%) relative to the total amount of the lubricant composition. [Appendix 24] The lubricant composition according to Appendix 23, wherein the average dispersed particle size (D50) of the surface-modified nanodiamond particles is 2 to 50 nm (preferably 4 to 30 nm, more preferably 6 to 25 nm, and even more preferably 10 to 20 nm). [Appendix 25] A lubricant composition according to any one of Appendices 13 to 22, wherein the content of the surface-modified nanodiamond particles is 0.1 to 2000 ppm by mass (preferably 0.2 to 1000 ppm by mass, more preferably 0.5 to 500 ppm by mass, and even more preferably 1.0 to 100 ppm by mass) relative to the total amount of the lubricant composition. [Appendix 26] The lubricant composition according to Appendix 25, wherein the average dispersed particle size (D50) of the surface-modified nanodiamond particles is 5 to 100 nm (preferably 8 to 80 nm, more preferably 10 to 60 nm, even more preferably 15 to 40 nm, and particularly preferably 18 to 35 nm). [Appendix 27] The lubricant composition according to any one of Appendices 13 to 26, wherein the content of the solvent is 90 to 99.9999 mass % based on the total amount of the lubricant composition. [Appendix 28] The lubricant composition according to any one of Appendices 13 to 27, wherein the content of the organic dispersion medium as a lubricant base in the total amount of the solvent is 60 mass% or more (preferably 70 mass% or more, more preferably 80 mass% or more, and even more preferably 90 mass% or more). [Appendix 29] The lubricant composition according to any one of Appendices 13 to 28, which has a haze value of 5 or less (preferably 3 or less, more preferably 1 or less). [Appendix 30] A lubricant composition according to any one of Appendices 13 to 29, wherein the combined content of the surface-modified nanodiamond particles and the lubricant base is 70 mass% or more (preferably 80 mass% or more, more preferably 90 mass% or more, even more preferably 95 mass% or more, and particularly preferably 99 mass% or more) relative to the total amount of the lubricant composition. [Appendix 31] The lubricant composition according to any one of Appendices 13 to 30, wherein the organic dispersion medium as the lubricant base is one or more selected from the group consisting of polyol esters, poly-α-olefins, mineral oils, alkylbenzenes, and polyalkylene glycols.

[0182] [Appendix 31] A method for producing a sliding member having a substrate and a carbon transfer film provided on the surface of the substrate, comprising sliding a sliding surface of the substrate and a sliding surface of a sliding member relative to each other in the presence of a lubricant composition according to any one of Appendices 13 to 30, and transferring carbon derived from nanodiamond particles in the lubricant composition onto the substrate to form the carbon transfer film. [Appendix 32] The method for producing a sliding member according to appendix 31, further comprising transferring a component in the base material onto the base material by the sliding, thereby forming the carbon transfer film. [Appendix 33] The method for producing a sliding member according to appendix 31 or 32, wherein the sliding member is made of a metal material. [Appendix 34] The method for producing a sliding member according to any one of Appendices 31 to 33, wherein the sliding is carried out under boundary lubrication conditions.

[0183] [Appendix 35] A piston having the carbon transfer film according to any one of Appendices 1 to 8 in a sliding area with a cylinder. [Appendix 36] A cylinder having the carbon transfer film according to any one of Appendices 1 to 8 in a sliding area with a piston. [Explanation of symbols]

[0184] 1 Sliding member 11 Base material 12 Carbon transfer film 13 Lubricant composition 14 Sliding members

Claims

1. s.p. 2 Carbon with bond and sp 3 The surface of the substrate is subjected to an elemental analysis using SEM-EDX measurement, and the ratio of zirconium therein is 0.6 mass% or less. The thickness of the substrate is less than 100 nm. 2 Carbon with bond and sp 3 sp for the sum of carbons with bonds 3 Ratio of carbon with bonds sp 3 / (sp 2 +sp 3 ) is 0.01 or more and 0.2 or less.

2. The sp 3 2. The carbon transfer film of claim 1, wherein the carbon having bonds is carbon from diamond.

3. The sp 2 3. The carbon transfer film of claim 1 or 2, wherein the carbon having bonds is carbon from diamond.

4. A substrate and a carbon transfer film provided on at least one surface of the substrate, The carbon transfer film is sp 2 Carbon with bond and sp 3 and carbon having bonds, and having a thickness of less than 100 nm; the proportion of zirconium calculated from elemental analysis by SEM-EDX measurement of the surface of the carbon transfer film is 0.6 mass % or less; s.p. 2 Carbon with bond and sp 3 sp for the sum of carbons with bonds 3 Ratio of carbon with bonds sp 3 / (sp 2 +sp 3 ) is 0.01 or more and 0.2 or less.

5. The sliding member according to claim 4 , wherein the carbon transfer film contains a component derived from the substrate.

6. The lubricant comprises an organic dispersion medium as a lubricant base, and nano-diamond particles nano-dispersed in the organic dispersion medium, and the zirconia content is less than 100 ppm by mass; The median diameter (D50) of the nanodiamond particles is 1 to 100 nm; A lubricant composition, wherein the nanodiamond particles are surface-modified nanodiamond particles having a surface modified with a group represented by the following formula (1): -X-R 1 (1) [In formula (1), X represents -O-, -O-C(=O)-, -C(=O)-O-, -C(=O)-NH-, or -S-, and the bond extending to the left from X is bonded to the nanodiamond particle. R 1 represents a monovalent organic group. The monovalent organic group is a substituted or unsubstituted monovalent hydrocarbon group; a substituted or unsubstituted monovalent heterocyclic group; or a group to which two or more of the monovalent hydrocarbon groups and / or the monovalent heterocyclic groups are bonded, and the bonded groups may be directly bonded or may be bonded via a linking group, and the linking group represents an amino group, an ether bond, an ester bond, a sulfide bond, a carbonyl group, an organic group-substituted amide group, an organic group-substituted urethane bond, an organic group-substituted imide bond, a thiocarbonyl group, or a group to which two or more of these are bonded, and the atom bonded to X is a carbon atom. However, in formula (1), the molar ratio of carbon atoms to the total amount of heteroatoms selected from the group consisting of nitrogen atoms, oxygen atoms, sulfur atoms, and silicon atoms is 4.5 or more.]

7. The R 1 The lubricant composition according to claim 6, wherein is a monovalent organic group that is free of a hydroxy group, a carboxy group, an amino group, a mono-substituted amino group, a terminal alkenyl group, and a terminal epoxy group.

8. 8. The lubricant composition according to claim 6, wherein the organic dispersion medium as the lubricant base is at least one selected from the group consisting of polyol esters, poly-α-olefins, mineral oils, alkylbenzenes, and polyalkylene glycols.

9. The lubricant composition according to any one of claims 6 to 8, wherein the content of the nanodiamond particles is 0.01 to 5.0 mass%, and the average dispersed particle size of the nanodiamond particles in the lubricant composition is 2 to 50 nm.

10. The lubricant composition according to any one of claims 6 to 9, wherein the content of the nanodiamond particles is 0.1 to 2000 ppm by mass, and the average dispersed particle size of the nanodiamond particles in the lubricant composition is 5 to 100 nm.

11. A method for manufacturing a sliding member having a substrate and a carbon transfer film provided on a surface of the substrate, comprising the steps of: A method for manufacturing a sliding member, comprising sliding a sliding surface of the substrate and a sliding surface of a sliding member relative to each other in the presence of the lubricant composition according to any one of claims 6 to 10, and transferring carbon derived from nanodiamond particles in the lubricant composition onto the substrate to form the carbon transfer film.

12. The method for producing a sliding member according to claim 11, further comprising the step of transferring a component in the base material onto the base material by the sliding, thereby forming the carbon transfer film.

13. The method for producing a sliding member according to claim 11 or 12, wherein the sliding member is made of a metal material.

14. The method for producing a sliding member according to any one of claims 11 to 13, wherein the sliding is carried out under boundary lubrication conditions.

15. A piston having the carbon transfer film according to any one of claims 1 to 3 in a sliding area with a cylinder.

16. A cylinder having the carbon transfer film according to any one of claims 1 to 3 in a sliding area with a piston.

Citation Information

Patent Citations

  • Sliding member and sliding system using the same

    JP2012246545A

  • Nanodiamond fluid dispersion and nanodiamond

    JP2017048083A

  • Nanodiamond-dispersed liquid and method for producing the same

    JP2017088449A

  • Surface modified nanodiamond and organic solvent dispersion thereof

    JP2017186234A

  • Surface-modified nanodiamond, dispersion comprising the surface-modified nanodiamond, and composite material

    JP2018140893A